Living a Post-Disaster Life: The Role of Cultural Adaptability, Coping Strategies, and Spiritual Support on Resilience Among Families Affected by the Semeru Eruption - Abdul Haris Fitri Anto (Da'wa Faculty of Islamic State University Salatiga, 2024)
This research delved into the key determinants influencing family resilience in the aftermath of the Semeru volcano eruption. Catastrophic events like volcanic eruptions often create immense psychological and material challenges for affected families. Using a qualitative approach, this study conducts in-depth interviews with families residing in the Huntap-Huntara resettlement area of Lumajang Regency. The findings highlight three essential components of family resilience—belief systems, organisational structure, and communication coupled with problem-solving abilities—which are crucial in helping families recover. These components are shaped by both internal and external factors, including 1) flexible roles and cultural adaptability, 2) disaster-specific coping strategies, and 3) religious and spiritual support. Despite the uneven distribution of aid and the challenges of relocation, these resilience factors enable families to navigate post-disaster life. The study offers insights for future research and suggests potential psychological interventions to strengthen family resilience in similar contexts.